2020
DOI: 10.1039/d0cp00549e
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between membrane permeation and partitioning of nitroaromatic explosives and their functional groups. A computational study

Abstract: Nitroaromatic explosives, such as 2,4,6-trinitrotoluene, are representative aromatic compounds, which are generally highly toxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Antiseptic Picloxydine, Octenidine, Miramistin [470], Polyhexamethylene Biguanide [471] Insecticide Parathione [132], Fipronil [472], Dibutyl succinate [203] Former Drugs d-sotalol, cisapride [473], piracetam (status varies among countries) [474], ORG-12962 [199] Toxic xenobiotic Polybrominated-diphenyl-ethers [475], Bisphenol [476], Perfluoroalkyls [477], nitroaromatic explosives (TNT,2A, and 24DA) [478][479][480][481], 1,4-Dioxane [482], Benzo[a]pyrene [483] Nanomaterials Graphene [484][485][486][487], Carbon Dots [488], Phosphorene Oxide Nanosheets [489], Gold Nanoparticles [490][491][492], Titanium Dioxide Nanoparticles [493], Generic Nanoparticles (coarse grained) [494], Fullerene [495][496][497][498], Previous reviews [499] Polymers Poly(ethyleneoxide)-Poly-(propylene oxide) [500], polyethylenimine [501], Poloxamer [502,503], Pluronics [504,505], poly(ethyleneglycol)-desferrioxamine/ gallium [506], PEG functionalized with carbochydrates [507] and peptides…”
Section: Application Xenobioticmentioning
confidence: 99%
“…Antiseptic Picloxydine, Octenidine, Miramistin [470], Polyhexamethylene Biguanide [471] Insecticide Parathione [132], Fipronil [472], Dibutyl succinate [203] Former Drugs d-sotalol, cisapride [473], piracetam (status varies among countries) [474], ORG-12962 [199] Toxic xenobiotic Polybrominated-diphenyl-ethers [475], Bisphenol [476], Perfluoroalkyls [477], nitroaromatic explosives (TNT,2A, and 24DA) [478][479][480][481], 1,4-Dioxane [482], Benzo[a]pyrene [483] Nanomaterials Graphene [484][485][486][487], Carbon Dots [488], Phosphorene Oxide Nanosheets [489], Gold Nanoparticles [490][491][492], Titanium Dioxide Nanoparticles [493], Generic Nanoparticles (coarse grained) [494], Fullerene [495][496][497][498], Previous reviews [499] Polymers Poly(ethyleneoxide)-Poly-(propylene oxide) [500], polyethylenimine [501], Poloxamer [502,503], Pluronics [504,505], poly(ethyleneglycol)-desferrioxamine/ gallium [506], PEG functionalized with carbochydrates [507] and peptides…”
Section: Application Xenobioticmentioning
confidence: 99%
“…First, hydrogen bonding between each of the drugs and water molecules was analyzed (Figure S10), as the impact of hydrogen bonding on permeation efficiency was previously reported in multiple studies. 11,62 It was shown that, generally, the larger the number of hydrogen bonds with water, the lower the permeation rate across the membrane, as the loss of hydrogen bonds between the permeant and water molecules results in an energetic penalty for the permeation pathway.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Yang et al . explored the influence of different functional groups on the permeation of nitroaromatic compounds, finding that the hydrogen bonding ability of the molecules is related to the permeability: the addition of polar groups decreases the permeability …”
Section: Introductionmentioning
confidence: 99%
“…The force constant of the harmonic spring was 1000 kJ mol –1 nm –2 for all windows, ensuring the adequate sampling of the simulations. Each window was run for 50 ns and the last 20 ns of trajectories were used for the calculation of PMF profiles . Due to membrane symmetry, we only calculated the free energy profiles from z = 4 nm to z = 0 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work found that the monoamino metabolites of TNT had higher transmembrane capacity than their parent compound, which helps to explain why they are even more toxic than TNT . It is still a challenge for experimental techniques to obtain a detailed molecular-level understanding of chemical–membrane interactions, and molecular simulation technology has been proved to be a useful tool for obtaining information about the penetration and distribution of small molecules in cell membranes and how they affect the properties of lipid bilayer membranes. ,, In the present work, we used the all-atom molecular dynamics (MD) method and umbrella sampling (US) technology to study the permeation process of RDX and DNAN mixtures, according to their molar ratio within IMX-104 formulation, from the water phase to the 1-palmitoyl-2-oleoyl- sn- glycerol-3-phosphocholine (POPC) phospholipid bilayer membrane, and investigate the effect of intermolecular interaction between RDX and DNAN on their entering into the membrane.…”
Section: Introductionmentioning
confidence: 99%